EVALUASI MENU ENGINEERING DALAM MENINGKATKAN PROFIT PENJUALAN MAKANAN D’COFFEE CUP WIYUNG - Fachrizal Rahardhika Murti; Lilis Sulandari; Niken Purwidiani; Qorry' Aina (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to evaluate the profitability and popularity of food menus, specifically the rice bowl category, at D'Coffee Cup Wiyung using the Menu Engineering method. The research employed a descriptive quantitative approach, analyzing sales data from July 2025, which included the contribution margin (CM) and sales volume of 15 menu items. The analysis results classified the menus into four quadrants: Stars, Plowhorses, Puzzles, and Dogs. The findings revealed that no menu was classified as a Star. A total of 4 menus (26.7%) were categorized as Plowhorses (popular but low profit), 7 menus (46.7%) as Puzzles (high profit but unpopular), and 4 menus (26.7%) as Dogs (unpopular and unprofitable). Based on this classification, distinct development strategies were formulated for each category, such as price review, targeted promotion, menu modification, and elimination. The study concludes that the application of menu engineering is effective as a data-driven analysis tool for increasing profitability through more directed managerial decision-making and portfolio optimization.